Decomposition and Insect Succession on Guinea Pig Carcass in Jaffna Sri Lanka - Chandrasegaran, T.; Gnaneswaran, R. (University of Jaffna, 2024)
Carrion insects visit the carcass in a predictable order depending on the different stages of decomposition, which is referred to as insect succession. Location and the position of the carcass affect the rate of decomposition and the pattern of insect succession. The objective is to study the differences in the rate of decomposition and insect succession patterns between the carcasses of a hanging and a ground-lying guinea pig. Two six-month-old, 500-gram-weighing male guinea pigs (Cavia porcellus) were sacrificed using identical methods. One (C1) was kept on the ground 100m away from the insectary, and the other (C2) was kept in a hanging position, 1.5m above the floor of the outside insectary. All the environmental parameters are similar except the roof shade for the hanging carcass. Morphological changes in the decomposing carcasses were noted, and insects visited the carcasses were collected twice a day till the carcasses were fully decomposed. Five stages of decomposition were differentiated, and the time taken for each stage was noted. The decomposition rate was higher in C1- ground lying carcass when compared with hanging carcass C2. A total of 27 species belonging to 15 families of the same orders were collected from C1, and 13 species of insects representing eight families of 4 orders were collected from C2. The insect succession on both C1 and C2 throughout the decomposition stages showed a similar pattern as Musca domestica was the first visitor at the fresh stage, followed by Chrysomya megacephala and Chrysomya rufifacies at their bloat stage. Coleopterans reached decay and post-decay stages. However, their arrival time was varied. C1 quickly changed into the following decomposition stage, completed the process, and reached the skeletonized stage in 31 days, but C2 took 37 days to complete. Dermestes maculatus is the only representative of Coleoptera for C2, but 07 Species of 6 families were found to be associated with C1. Differences in decomposition rate between hanging and ground-lying carcasses could be caused by the differences in drying and availability of ground-dwelling taxa in hanging carcasses.
Keywords: Carrion insects; Insect succession; Carcass; Decomposition